Oxidative Stress and Antioxidant Enzyme Activities in Patients with Cutaneous Leishmaniasis in Endemic Region of Hatay (ANTIOCH) - CULHA, GULNAZ; YALIN, ERDINC; YALIN, SERAP; EROGLU, PELIN; BERKOZ, MEHMET (Asian Journal of Chemistry, 2010)
Leishmania is the collective name for a number of disease caused by protozoon flagellates of genus Leishmania which have diverse clinical manifestations. In this study, we investigated the effect of free radicals and antioxidants on cutaneous leishmaniasis (CL). Venous blood samples of patients and controls were collected and analyzed for serum nitric oxide (NO) and malondialdehyde (MDA) levels, superoxide dismutase (SOD) and catalase (CAT) activities. 53 treated CL patients, 42 untreated patients and 30 healty control subjects wereenrolled in this study. The levels of MDA and NO showed a significant increase (p < 0.05) in the untreated patients when compared to the treated patients and control groups. In the untreated group, the activities of both SOD and CAT were found to be decreased (p < 0.05) compared with values in the control and treated groups. After the treatment, NO and MDA levels were decreased whereas the activities of CAT and SOD were increased. These results provide some evidence for a potential role of increased lipid peroxidation and decreased enzymatic antioxidants in cutaneous leishmaniasis. These results suggested that oxidant stress plays an important role in the pathogenesis of cutaneous leishmaniasis.